OPTIMAL (T, S)-POLICIES IN A DISCRETE-TIME OPPORTUNITY-BASED AGE REPLACEMENT: AN EMPIRICAL STUDY - DOHI, T.; KAIO, N.; OSAKI, S. (Advanced Reliability Modeling II, 2006)
In this paper we consider the optimal (T, S)-policies in a discrete-time opportunity-based age replacement (DOAR), where S is a restricted duration of opportunities and T (≥ S + 1) is a preventive age replacement time. Based on the expected cost per unit time in the steady-state as a criterion of optimality, we formulate totally 6 DOAR models and derive numerically the optimal (T, S)-policies minimizing the respective expected costs per unit time. A numerical example with real failure time data investigates the dependence of the optimal DOAR policies and their associated minimum expected costs on parameters of the discrete Weibull failure time distribution.